2006
DOI: 10.1016/j.freeradbiomed.2005.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase inhibition counteracts nitrosative stress and poly(ADP-ribose) polymerase activation in diabetic rat kidney and high-glucose-exposed human mesangial cells

Abstract: Both increased aldose reductase (AR) activity and oxidative/nitrosative stress have been implicated in the pathogenesis of diabetic nephropathy, but the relation between the two factors remains a subject of debate. This study evaluated the effects of AR inhibition on nitrosative stress and poly(ADPribose) polymerase (PARP) activation in diabetic rat kidney and high-glucose-exposed human mesangial cells. In animal experiments, control (C) and streptozotocin-diabetic (D) rats were treated with/without the AR inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 81 publications
7
60
0
6
Order By: Relevance
“…Thus, pharmacological studies in diabetic animal models revealed importance of hyperglycemia, increased aldose reductase and protein kinase C activities, impaired neurotrophic support, as well as oxidative stress and PARP activation, in thermal hyper-and hypoalgesia associated with PDN. Taking into consideration, that hyperglycemia as well as AR and PARP activation lead to enhanced nitrotyrosine formation in tissue sites for diabetic complications (Cheung et al, 2005;Drel et al, 2006b;El-Remessy et al, 2003;Ho et al, 2006;Obrosova et al, 2005c) including PNS (Ho et al, 2006;Obrosova et al, 2005a,c;Szabo et al, 2006), these findings are quite consistent with the present study implicating nitrosative stress in thermal hypoalgesia in STZ-diabetic mice. Note, that oxidative stress leads to peroxynitrite formation both directly (reaction between superoxide and nitric oxide) and indirectly, via downregulation of superoxide dismutase and resultant impairment of superoxide anion radical neutralization (Stevens et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, pharmacological studies in diabetic animal models revealed importance of hyperglycemia, increased aldose reductase and protein kinase C activities, impaired neurotrophic support, as well as oxidative stress and PARP activation, in thermal hyper-and hypoalgesia associated with PDN. Taking into consideration, that hyperglycemia as well as AR and PARP activation lead to enhanced nitrotyrosine formation in tissue sites for diabetic complications (Cheung et al, 2005;Drel et al, 2006b;El-Remessy et al, 2003;Ho et al, 2006;Obrosova et al, 2005c) including PNS (Ho et al, 2006;Obrosova et al, 2005a,c;Szabo et al, 2006), these findings are quite consistent with the present study implicating nitrosative stress in thermal hypoalgesia in STZ-diabetic mice. Note, that oxidative stress leads to peroxynitrite formation both directly (reaction between superoxide and nitric oxide) and indirectly, via downregulation of superoxide dismutase and resultant impairment of superoxide anion radical neutralization (Stevens et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Accumulation of nitrotyrosine [NT, a footprint of peroxynitrite-and other reactive nitrogen species (RNS)-induced protein nitration] has been documented in vascular endothelium (Pacher et al, 2005;Szabo et al, 2002b), myocardium (Pacher et al, 2005), retina (Cheung et al, 2005;Obrosova et al, 2005c), and kidneys (Drel et al, 2006b) of streptozotocin-diabetic rats and mice as well as cutaneous microvascular endothelium (Szabo et al, 2002b), myocardium (Frustaci et al, 2000), and kidneys (Thuraisingham et al, 2000) of human subjects with diabetes. Increased NT immunoreactivity has also been demonstrated in peripheral nervous system i.e., peripheral nerve, spinal cord and dorsal root ganglion (DRG) neurons, of STZ-diabetic rats (Cheng and Zochodne, 2003;Obrosova et al, 2005a) and STZ-diabetic (Ho et al, 2006;Obrosova et al, 2005b), ob/ob (Drel et al, 2006a), and high-fat diet fed mice (Obrosova et al, 2007b), and epineurial vessels of STZ-diabetic, ZDF diabetic fatty, and Zucker fatty rats (Coppey et al, 2001;Obrosova et al, 2005a,b;Oltman et al, 2005).…”
mentioning
confidence: 99%
“…Nitrosative stress in both diabetic retina and retinal vascular cells was prevented by fidarestat. The latter is consistent with the alleviation of peroxynitriteinduced injury by AR inhibition in aorta, peripheral nerve, vasa nervorum, renal cortex, and retina of STZ-diabetic rats with a shorter duration of diabetes and high glucose-exposed human Schwann and bovine endothelial cells in previous studies by our group (15,16,51).…”
Section: Discussionsupporting
confidence: 91%
“…Fidarestat at least partially prevented diabetes-induced increase in kidney weight as well as nitrotyrosine (a marker of peroxynitrite-induced injury and nitrosative stress), and poly(ADP-ribose) (a marker of polymerase activation) accumulation in glomerular and tubular compartments of the renal cortex. These results indicate that fidarestat treatment counteracts nitrosative stress and polymerase activation in the diabetic renal cortex and high-glucose-exposed human mesangial cells [24].…”
Section: Nephropathymentioning
confidence: 65%
“…As described above, for example, the loss of mesangial cell contractile responsiveness in high glucose-induced rat mesangial cells resulted from the activation of the polyol-pathway could be mediated by altered PKC activity [14]. In vitro studies on cultured human mesangial cells and in vivo studies in the diabetic renal cortex of streptozotocin-diabetic rats have indicated the presence of both increased AR activity and oxidative/nitrosative stress in the pathogenesis of diabetic nephropathy, and the nitrosative stress and polymerase activation could be counteracted by AR inhibition [24]. Moreover, the increased kinase activation, depletion of reduced glutathione, increased superoxide accumulation, and DNA damage could be prevented by AR-deficiency in the amelioration of motor nerve conduction velocity [16].…”
Section: The Polyol Pathwaymentioning
confidence: 99%